Physical and cognitive-based training in healthy older adults: Evidence from a systematic review and meta-analysis - Fatemeh Adelirad; Zeinab Javadivala; Iman Dianat; Aysan Amrahi Tabieh; Vijay Kumar Chattu (BioSocial Health Journal)
Introduction: Several studies have shown that cognitive training interventions and regular physical activity are popular intervention in dementia prevention guidelines. The purpose of this study was to examine the effectiveness of physical and mental training on cognitive outcomes in, older adults. Methods: For this systematic review and meta-analysis, randomized clinical trials (RCTs) published between 2000 and 6 February 2023 were extracted from several electronic databases, including, ProQuest, PubMed, Scopus, Embase, and Web of Science. Results: The meta-analysis included 36 studies. The results indicated that the pooled MD for cognition was 0.49 (95% CI=0.28 to 0.70, I2=79.3%, P=0.0001) and both physical and mental training have a "large to larger" effect on Episode memory (pooled MD: 1.98; 95% CI=1.20 to 2.77, I2=92%, P=0.001). Also, as a result, the trainings had a "small to larger" impact on the executive function of older adults (pooled MD: 0.64; 95% CI=0.26 to 1.02, I2=86.2%, P=0.0001). Conclusion: Our controversial results indicated that the non-pharmacological physical-mental training improves executive function which that can affect the ability of elders, while did not support the improvement of attention, processing speed, and verbal memory.